2021
DOI: 10.3390/biom11020236
|View full text |Cite
|
Sign up to set email alerts
|

The Ins and Outs of RAS Effector Complexes

Abstract: RAS oncogenes are among the most commonly mutated proteins in human cancers. They regulate a wide range of effector pathways that control cell proliferation, survival, differentiation, migration and metabolic status. Including aberrations in these pathways, RAS-dependent signaling is altered in more than half of human cancers. Targeting mutant RAS proteins and their downstream oncogenic signaling pathways has been elusive. However, recent results comprising detailed molecular studies, large scale omics studies… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(62 citation statements)
references
References 170 publications
8
44
0
Order By: Relevance
“…Labelling conditions were optimised and levels of protein biotinylation assessed in whole cell lysates as well as streptavidin eluate material to control for consistency (Fig 1D). Previous proteomics-based studies exploring the KRAS "proximitome", based on BioID, revealed many shared proteins between WT & mutant KRAS (mainly G12V, S17N, C185S), predominantly involved in protein expression and trafficking (Kiel et al, 2021;Li et al, 2012;Matallanas et al, 2003). Additionally, there appears to be a large overlap between GTP/GDP KRAS interactors (proteins in closed proximity), indicating a more gradual KRAS activation transition rather than being an on/off switch.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Labelling conditions were optimised and levels of protein biotinylation assessed in whole cell lysates as well as streptavidin eluate material to control for consistency (Fig 1D). Previous proteomics-based studies exploring the KRAS "proximitome", based on BioID, revealed many shared proteins between WT & mutant KRAS (mainly G12V, S17N, C185S), predominantly involved in protein expression and trafficking (Kiel et al, 2021;Li et al, 2012;Matallanas et al, 2003). Additionally, there appears to be a large overlap between GTP/GDP KRAS interactors (proteins in closed proximity), indicating a more gradual KRAS activation transition rather than being an on/off switch.…”
Section: Discussionmentioning
confidence: 99%
“…First, KRAS interacting partners were divided into several categories including receptors, activators, repressors, interactors and canonical RAS effectors proteins (Kiel et al, 2021). Additionally, to "benchmark" our results, the BioGRID (https://thebiogrid.org/) database was used to retrieve the previously known KRAS 'proximitome' ( Adhikari and Counter, 2018;Bigenzahn et al, 2018).…”
Section: Apex-2 Labelling Reveals Differential Molecular Environments Between Wt and Kras Mutantsmentioning
confidence: 99%
“…In the GTP-bound form, Ras switches into a conformation where it can bind and activate effector proteins, building different signaling networks at the membrane of cells, bridging extracellular cues into cellular events that regulate almost any aspect of cellular physiology, such as cell growth, proliferation, differentiation, and survival, having a decisive role in the acquisition of an oncogenic phenotype by healthy cells [9]. Activating mutations in Ras proteins diminishes their ability to hydrolyze the bound GTP to GDP, thus rendering it constitutively active even in the absence of receptor engagement.…”
Section: Introductionmentioning
confidence: 99%
“…RAS proteins often have been described as molecular switches that cycle between GDP-bound off and GTP-bound on states. When switched on by the (normally receptor-induced) exchange of GDP versus GTP, they can bind to an array of >20 different types of effector proteins which mediate the downstream biochemical and biological effects of RAS [2,3]. Oncogenic mutations keep RAS proteins in the GTP bound state resulting in the constitutive activation of pathways that stimulate cell proliferation, survival, invasiveness and drug resistance.…”
Section: Introductionmentioning
confidence: 99%